Medical Students' Voluntary Service During the COVID-19 Pandemic in Poland - Domaradzki, Jan; Walkowiak, Dariusz (Frontiers in Public Health, 2021)
From the very first moment coronavirus struck, medical students volunteered to support healthcare professionals' fight against the COVID-19 pandemic. To learn more about future healthcare professionals' volunteering during such an outbreak, we conducted a survey among 417 students of Poznan University of Medical Sciences. Our findings suggest that although numerous studies demonstrate that traditional, value-based volunteering is decreasing, and especially higher education students are more oriented toward their own career, in the times of the current health crisis, young peoples' involvement in volunteering has been mainly driven by altruism and the ethical imperative to serve their community, their fellow healthcare professionals and their patients. Thus, while the prime role of the volunteering was to relieve the healthcare system, it also reinforced such important medical values as altruism, public service and professional solidarity. Moreover, it proved that whilst risk is inherent to medicine, the students' volunteering is truly a moral enterprise.